Capital, conflict and convergence: a political understanding of neoliberalism and its relationship to capitalist transformation. Issue 6 (19th September 2019) - Carroll, Toby; Gonzalez-Vicente, Ruben; Jarvis, Darryl S. L.
ABSTRACT: In this article we argue against influential analyses of neoliberalism that prioritize variegation and the role of ideas as key theoretical foci relevant to understanding neoliberalism's diffusion into myriad national and political settings. Rather, we contend that crucial to understanding neoliberalism is the role of politically-produced convergence around market rationality that reflects two core processes: the reorganization of production and the ascendency of financialization. We present a theorization and analysis of neoliberalism's political production and diffusion over time, explaining its contested evolution and impact across diverse settings (both 'North' and 'South') and emphasizing its ever-intensifying symbiotic relationship with the consolidating world market in which the former has increasingly come to serve as the latter's operating system (OS) . Further, we posit that neoliberalism's form, function and impact demand analytically prioritizing the leverage of constellations of ideological and material interests within the contradictory context of consolidating relations of production and financialization. Our analysis thus challenges many previous expositions of neoliberalism for their failure to locate neoliberalism's manifestation as arising out of social conflict within particular junctures that privilege certain social forces and ideas over others. We also distinguish our position by highlighting how manifestations of neoliberalism in various settings have combined to yield a greater world market in which variegation has gradually given way to ever-intensifying disciplinary pressures towards market-policy conformity (mono-policy). While current populist movements may well turn out to be important counter movements to neoliberal hegemony, especially if they can internationalize, the disciplining effect of the world market renders many nationally-oriented policy alternatives costly and politically fraught.